Locally resolved large scale phase separation in polymer:fullerene blends. Issue 4 (12th January 2016) - Kästner, Christian; Seeland, Marco; Egbe, Daniel A. M.; Hoppe, Harald
Abstract : Large scale phase separation in polymer:fullerene bulk heterojunction solar cells investigated by electroluminescence imaging (ELI) and light-beam induced current (LBIC) measurements. Abstract : We report a comprehensive study probing the influence of polymer blending on the large scale phase separation by the use of electroluminescence imaging (ELI) and light-beam induced current (LBIC) measurements. The study is based on a semi-crystalline and an amorphous analogue of anthracene-containing poly( p -phenylene-ethynylene)- alt -poly( p -phenylene-vinylene) (PPE–PPV) copolymer (AnE-PVs) blended with [6, 6]-phenyl-C61-butyric acid methyl ester (PCBM). Since the semi-crystalline polymer AnE-PV ab strongly phase separates from PCBM, whereas the amorphous polymer AnE-PV ba intimately mixes with PCBM, the phase separation is precisely controlled by blending both polymers in distinct ratios. The analysis of electroluminescence images and light-beam induced current scans allowed us to conclude about the domain size of the phase separated bulk material and intermixed regions, respectively, with the advantage of probing the whole active layer of the device at once.